Studies on Some Lanthanide(III) Complexes of (Substituted)-Oxaminoacetyl Thiazoles - V. Muley, Damayanti (Asian Journal of Chemistry, 2016)
Proton-ligand dissociation constants of substituted oxaminoacetyl thiazoles and stability constants of their complexes with lanthanides have been determined pH-metrically, in 75-25% diaxane-water (v/v) mixture at 30°C and at ionic strength 0.1 M NaClO4 using Calvin-Bjerrum titration technique. These compounds form complexes by deprotonation.